Perceptions, beliefs, and anticipations regarding living wills among Master’s degree nursing students in China: an exploratory qualitative study - Yishan Yan; Ling Liu; Yue Wang; Wanmin Qiang (BMC Nursing, 2024)
Abstract Background Steeped in cultural heritage, the Chinese traditionally equate death with misfortune. This deeply rooted belief has led to a low rate of living will signings and poses challenges for implementing death education. Master’s degree nursing students are instrumental in facilitating and promoting the adoption of living wills, leveraging their specialized knowledge in providing compassionate care. Despite existing research on living wills, there is a scarcity of qualitative studies that consolidate the perceptions, beliefs, and anticipations of Master’s degree nursing students regarding living wills. Aim To scrutinize the perceptions, beliefs, and anticipations regarding living wills among Master’s degree nursing students in China. Method This study followed Colizzi’s phenomenological research method. An exploratory qualitative descriptive approach was employed, utilizing semi-structured face-to-face interviews. Thirteen participants participated in focus group interviews. The research question was: “What is your perception on living wills?”. Results Three main themes and eight subthemes were identified: Perceptions of living will (high attention, knowledge deficit, and lack of education), beliefs of living wills (high acceptance and positive clinical significance), and anticipations of the living will (high expectations of improved knowledge, factors influencing promotion, and suggestions for improvement). Conclusion The facilitation and progression of living wills is an intricate and drawn-out process, encountering obstacles at various stages. These insights are significant for policymakers and healthcare systems, emphasizing the necessity to cultivate a supportive environment for the establishment of living wills. As indispensable contributors to the clinical operations team, Master’s degree nursing students are required to possess relevant perceptions and to foster a constructive belief system.